Genotypes by Environment interaction of Groundnut (Arachis hypogaea L.) for Yield and Yield related components - Umata, Habte Berhanu; Hunduma, Adugna (Central Research Institute For Agriculture, 2024)
Groundnut is a versatile and economically significant plant that has played a prominent role in human history. Using additive main effects and multiplicative interaction analysis, the performance of 12 groundnut genotypes was assessed in six environments across four sites. Highly significant genotypes and GE interactions were found in the mean squares of the analysis of variance for seed yield per hectare. Environment-related differences made for 53.25% of the overall variation, whereas genotype was responsible for 43.73% of it. For 84.93% of the overall variation, the biplot was responsible. The most stable models according to the AMMI model were 19748 and 19750. As a result, these genotypes are thought to be the most suitable ones for the study locations. The candidate variety 19748 is stable and high yielding, with a yield advantage of about 18 percent above the standard check Babile-2.Then suggested to release and further multiply as a commercial variety at study and similar agro-ecology.